Information Service Modules to Improve Self-Control in The Prevention of Pornography - Febriella Fauziah; Zikry Latupasjana (TheraEdu: Journal of Therapy and Educational Psychology, 2025)
The phenomenon of pornography that occurs involves many adolescent ranging from owning pornographic videos, being victims of pornography, to becoming perpetrators of pornographic crimes. This reality is disappointing as the next generation of the nation. This study aims to develop the usability and feasibility of information service modules to improve self-control in the prevention of pornography. This research was conducted by testing research products by experts. The data from the study were analyzed using descriptive analysis and non-parametric statistics. The module usability test was analyzed using the Kendall's W concordance coefficient test to determine the alignment and consistency of the assessor. The results showed that the feasibility and use in the field in the information service module to improve self-control in the prevention of pornography can be used for counselor in schools. Thus, the prototype of an information service module to improve self-control in the prevention of pornography can be used as a valid, practical, and effective medium in improving self-control for the prevention of pornography that is worthy of use by the Counselor.